2009
DOI: 10.1177/0956247809103026
|View full text |Cite
|
Sign up to set email alerts
|

The slowing of sub-Saharan Africa's urbanization: evidence and implications for urban livelihoods

Abstract: According to data from the most recent inter-census period, some sub-Saharan African countries are now urbanizing very slowly. Actual decreases in the level of urbanization are rare, but have been recorded for Zambia (where counter-urbanization began in the 1980s) and Côte d'Ivoire and Mali (where there is evidence of counter-urbanization during the 1990s). Countries where urbanization levels are stagnating or increasing very slowly, especially when considering large and medium-sized towns, include Benin, Moza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
128
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(134 citation statements)
references
References 12 publications
4
128
0
1
Order By: Relevance
“…Although debate exists over whether Africa can be accurately classified as the fastest urbanising region of the world (see Potts, 2009;Satterthwhaite, 2010), it is undoubtedly true that many more Africans now live in urban areas than at any other point in history. The World Bank predicts that by 2030 Africa will finally be an urban continent, with more than 50% of its population living in cities (Kessides, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although debate exists over whether Africa can be accurately classified as the fastest urbanising region of the world (see Potts, 2009;Satterthwhaite, 2010), it is undoubtedly true that many more Africans now live in urban areas than at any other point in history. The World Bank predicts that by 2030 Africa will finally be an urban continent, with more than 50% of its population living in cities (Kessides, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Beauchemin and Bocquier (2004) challenge this assumption, and show the fall of urban fertility rates in a number of African cities in the 1980s and 1990s, as a result of movement in itself as well as the adaptation to urban fertility regimes. Signs of falling urban fertility rates are confirmed on a cross-country basis in more recent Demographic Health Surveys (Potts 2009;2012b). The distribution of the urban population has shifted towards larger urban areas over the past few decades and this is also likely to affect fertility behaviour over time, as smaller urban areas maintain fertility rates and child mortality rates closer to those of rural areas (Montgomery 2008;Tacoli 2012).…”
Section: Rural Annual Growth Ratementioning
confidence: 80%
“…Further systematic empirical research by Potts (2005Potts ( , 2006Potts ( , 2009Potts ( , 2012a has continued to show that the notion of rapid urbanisation in Africa no longer holds true as presented by several reports including the World Bank (2009) Developmental Report. It is shown that there is much variation in the urbanisation patterns of countries South of Sub Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…In Kenya, Potts (1995Potts ( , 2005Potts ( , 2006Potts ( , 2009Potts ( , 2012a has shown evidence of declining rates of urbanization in most of sub-Saharan Africa while in Malaysia there is evidence of de-industrialization due to depleting oil and gas resources. However while the factors behind de-urbanisation in both countries are different, there are lessons that Kenya can learn from Malaysia's industrialization, subsequent urbanization and now de-industrialization process.…”
Section: Introductionmentioning
confidence: 99%